2019
DOI: 10.1002/ijc.32684
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic serum sCD27 and sCD30 in serial samples and risks of non‐Hodgkin lymphoma subtypes

Abstract: Elevated prediagnostic serum levels of the immune activation markers sCD27 and sCD30 have been associated with non-Hodgkin lymphoma (NHL). However, the use of a single sample per participant in these studies has limited etiologic inferences. We report findings, overall and by NHL subtype, from a case-control analysis (422 cases, 434 controls) within the Janus Serum Bank with two samples per subject collected on average 5 years apart. Chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In an attempt to include all published nested case-control studies investigating NHL and prediagnostic concentrations of these immune markers that were conducted in general population cohorts (eg, excluding cohorts of subjects with HIV/AIDS), we sought to also include data from studies conducted within the Janus Serum Bank, the Northern Sweden Health study and the European Prospective Investigation into Cancer and Nutrition study. 23,24,27 However, this could not be accomplished due to data sharing restrictions related to the European Union General Data Protection Regulation Policy. 30 It is notable that many of the studies included in our pooled analysis used different assays, and/or the same assays at different points in calendar time, to measure the same immune markers (Table S1).…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…In an attempt to include all published nested case-control studies investigating NHL and prediagnostic concentrations of these immune markers that were conducted in general population cohorts (eg, excluding cohorts of subjects with HIV/AIDS), we sought to also include data from studies conducted within the Janus Serum Bank, the Northern Sweden Health study and the European Prospective Investigation into Cancer and Nutrition study. 23,24,27 However, this could not be accomplished due to data sharing restrictions related to the European Union General Data Protection Regulation Policy. 30 It is notable that many of the studies included in our pooled analysis used different assays, and/or the same assays at different points in calendar time, to measure the same immune markers (Table S1).…”
Section: Study Populationmentioning
confidence: 99%
“…The markers most consistently associated with NHL include soluble CD27 (sCD27) and sCD30, which are cleaved fragments of the lymphocyte transmembrane proteins CD27 and CD30 measured as markers of immune activation, and chemokine ligand-13 (CXCL13), a B cell chemoattractant to secondary lymphoid tissue. [15][16][17][18][19][20][21][22][23][24][25][26][27] Most studies have reported that elevated levels of these three immune markers are associated with increased subsequent risk of NHL, although it is unclear to what extent these associations vary by lymphoma subtype or reflect early disease-induced effects, as has been suggested by some longitudinal studies. 24,25,28 The precise time frame that would reflect disease-induced rather than etiologic effects is not known for most subtypes; the known differences in the aggressiveness of pathogenesis between, for example, the aggressive DLBCL subtype and the more indolent subtypes like CLL/SLL, FL or MZL suggest subtype-specific variability in the preclinical stages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, haematological malignancies and glioma have some common aetiological pathways, such as exposure to ionising radiation and an inverse relationship with asthma and allergies 7 . In lymphoma studies, analysis of several relevant proteins, including sCD23, sCD27, sCD30 and CXCL13, in pre‐diagnostic plasma samples have shown a significant difference between cases and controls even several years before diagnosis 8,9 . However, little is known about how the subclinical immunologic perturbations influence glioma risk.…”
Section: Introductionmentioning
confidence: 99%